Cancer of the Nervous System. - Black, Peter M. (Wolters Kluwer Health, 2011)
Thoroughly revised to reflect the latest advances in neurosurgery, radiation oncology, chemotherapy, biological therapy, and the basic sciences, the Second Edition of this highly acclaimed volume is the most comprehensive, current reference on tumors of the central and peripheral nervous system. More than 100 of the foremost authorities present multimodality treatment strategies for specific tumor types and examine the mechanisms of tumorigenesis. Coverage includes state-of-the-art information on image-guided surgery, local delivery systems, intraoperative imaging, proton beam therapy, conform.